2022
DOI: 10.1021/acs.est.2c04232
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Design of the Polyamide Layer Structure of Nanofiltration Membranes by Sacrificing Hydrolyzable Groups toward Enhanced Separation Performance

Abstract: Nanofiltration (NF) is an effective technology for removing trace organic contaminants (TrOCs), while the inherent trade-off effect between water permeance and solute rejections hinders its widespread application in water treatment. Herein, we propose a novel scheme of "monomers with sacrificial groups" to regulate the microstructure of the polyamide active layer via introducing a hydrolyzable ester group onto piperazine to control the diffusion and interfacial polymerization process. The achieved benefits inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…To emphasize the significance of substrate properties (especially the pore size) in enhancing membrane performance for micropollutant removal and also highlight the membrane superiority conferred by the MOF interlayer, several commercial membranes and our prepared membranes were evaluated for the rejections of six representative OMPs (Figure c). The rejection characteristics for OMPs by NF membranes were jointly determined by the size exclusion, electrostatic effects, and hydrophobicity interactions. ,, It can be seen that the three commercial membranes (DF30, NF270, and VNF2) could not sufficiently reject the OMP with low-molecular weight, positive charges, or/and high hydrophobicity (i.e., nalidixic acid, trimethoprim, and carbamazepine). Affected by the substrates, the prepared TFC 150 membranes exhibited OMP rejections in the range of 87.1–96.0%, remarkably more superior to those of TFC 300 (66.4–89.5%).…”
Section: Resultsmentioning
confidence: 99%
“…To emphasize the significance of substrate properties (especially the pore size) in enhancing membrane performance for micropollutant removal and also highlight the membrane superiority conferred by the MOF interlayer, several commercial membranes and our prepared membranes were evaluated for the rejections of six representative OMPs (Figure c). The rejection characteristics for OMPs by NF membranes were jointly determined by the size exclusion, electrostatic effects, and hydrophobicity interactions. ,, It can be seen that the three commercial membranes (DF30, NF270, and VNF2) could not sufficiently reject the OMP with low-molecular weight, positive charges, or/and high hydrophobicity (i.e., nalidixic acid, trimethoprim, and carbamazepine). Affected by the substrates, the prepared TFC 150 membranes exhibited OMP rejections in the range of 87.1–96.0%, remarkably more superior to those of TFC 300 (66.4–89.5%).…”
Section: Resultsmentioning
confidence: 99%
“…The results of our previous studies proved that the overall rejection capacity of an NF membrane for organic micropollutants (OMPs) could be strongly correlated with its xylose rejection, despite the certain differences among the OMP properties. 32,44,45 By adding eight PhACs into the tap water for rejection tests, it was indeed demonstrated that the R60−H5 and R60−H120 membranes of higher water permeance were equivalently effective in removing those PhACs with the R60 membrane (Figure 5d). Due to the electrostatic interactions, the rejections of the negatively charged PhACs were slightly higher than those of the positively charged ones with a similar range of molecular weights.…”
Section: Membrane Performance Evaluation Pertaining To Practical Appl...mentioning
confidence: 99%
“…In addition, to further enhance the membrane surface positive charge density, a higher PIP concentration in the aqueous phase than the normal use (<1.0 wt %) was adopted, which is favorable for their diffusion into the organic phase and the ensuing preservation of amine groups in the as-synthesized active layer. In the literature, the mixed monomer approach has been extensively investigated, exemplified by adding acidic monomers such as 3,5-diaminobenzoic acid, 29 taurine, 30 and piperazine-2-carboxylic acid methyl ester 31 into the aqueous phase and by adding asymmetric monomers such as trimellitic anhydride chloride 32 into the organic phase, mostly with a main purpose of enhancing the membrane surface negative charge density. The approach reported in the current study is thus very different from the above approaches in that it aims to prepare negative-charge-reduced NF membranes.…”
Section: Introductionmentioning
confidence: 99%